Adsorption of Methylene Blue from Aqueous Solutions on Carbon Coated Monolith - Darmadi, Darmadi; Choong, Thomas SY; T.G, Chuah; Yunus, Robiah; Yap, Y.H Taufiq (ASEAN Journal of Chemical Engineering, 2008)
Carbon coated monolith was used as adsorbent to remove methylene blue from aqueous solution. Adsorption rate and equilibrium parameters of methylene blue were investigated in a batch system. Equilibrium adsorption data were predicted by two isotherms, i.e. the Langmuir and the Freundlich isotherms. The best fit to the data was obtained with the Langmuir isotherm with maximum monolayer adsorption capacity of 191.307 mg/g. Kinetics of adsorption with respect to the initial concentration of dye was described by using both the pseudo-first-order and pseudo-second-order models. It was found that kinetic data fitted well with the pseudo-first-order model.